A Study of the Relationship between Human Resource Practices and Turnover Intention among Chinese Millennial Employees, with Mediation of Job Embeddedness - Hu, Xinyu (2022)
As millennials (those born in the 1980s and 1990s) grow up, they are becoming a major force in the workplace and playing important roles in many positions. Especially in China, there are a large number of millennials with distinct personalities. However, they frequently change their jobs in the workplace, which not only brings high management costs to the company, but also affects the stable development of the company. Therefore, this paper takes Chinese millennial employees as the research object to explore the impact of compensation, growth opportunities and training in human resources practices on their turnover intention, as well as the impact of job embeddedness on their turnover intention. In addition, this paper also explores the role of job embeddedness as a mediating variable in mediating the effects of compensation, growth opportunities and training on the turnover intention, respectively. Through an empirical study of 284 Chinese millennial employees, it is found that compensation, growth opportunities, training and job embeddedness are significantly negatively correlated with their turnover intention, respectively. Besides, job embedment plays a mediating role in the relationship between compensation, growth opportunities and training on turnover intention of Chinese millennial employees.